2009
DOI: 10.1177/000348940911801205
|View full text |Cite
|
Sign up to set email alerts
|

Study of Vestibular Evoked Myogenic Potentials in Patients Affected by Meniere's Disease Treated with Endolymphatic Mastoid Shunt

Abstract: We conclude that VEMPs are a clinically useful tool in the postoperative follow-up of patients with an EMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The incidence of MD affecting bilateral ears has been shown in the literature to be approximately 30%. 8,9 Greven and Oosterveld reported that as high as 73% of patients with MD experience tinnitus or hearing loss of the contralateral ear. 10 A study in Japan performed histological analysis of temporal bones and found the incidence of bilateral MD to be 30%.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of MD affecting bilateral ears has been shown in the literature to be approximately 30%. 8,9 Greven and Oosterveld reported that as high as 73% of patients with MD experience tinnitus or hearing loss of the contralateral ear. 10 A study in Japan performed histological analysis of temporal bones and found the incidence of bilateral MD to be 30%.…”
Section: Introductionmentioning
confidence: 99%